Comparison of the Effectiveness of Transactional Analysis Therapy and Narrative Therapy on Fear of Intimacy in Women Affected by Marital Infidelity - Fazel Hamedan, Naghmeh; Oraki, Mohammad; Azadi, Mehran (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The aim of the present study was to compare the effectiveness of Transactional Analysis Therapy and Narrative Therapy on the fear of intimacy in women affected by marital infidelity.Methods and Materials: The research method was quasi-experimental with a pre-test, post-test design and a control group with a follow-up period. The statistical population of this study included all women affected by their spouses' infidelity who referred to counseling centers in District 4 of Tehran in 2022. A total of 45 participants were selected through purposive sampling and randomly assigned to two experimental groups and one control group. The instrument used in this research was Pollard's Fear of Intimacy Scale (IFS) (1998). The intervention included Eric Berne's Transactional Analysis (1950) and White's Narrative Therapy protocol (2017), conducted in 8 group sessions of 120 minutes each, twice a week, for the first and second experimental groups. Data were analyzed using mixed ANOVA.Findings: The results of the analysis showed a significant difference in the fear of intimacy between the groups in the post-test and follow-up (P